2001
DOI: 10.1136/bjo.85.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome of ocular adnexal lymphoma subtyped according to the REAL classification

Abstract: Aim-To classify ocular adnexal lymphomas according to the Revised European and American Lymphoma (REAL) classification and to determine any correlation between clinical features or histomorphological variables with the patients' outcome. Methods-Conventional and immunohistology were performed on representative sections of 53 specimens of 46 patients with ocular adnexal lymphoma. The antibodies used were CD20, BCL-2, CD21, CD23, CD43, CD3, CD5, p53, cyclin D1, pan-cytokeratin, kappa, lambda, IgD, and IgM. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
124
2
12

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(150 citation statements)
references
References 18 publications
12
124
2
12
Order By: Relevance
“…29,87,88 In all published series except that by Cho et al, 42 the median age was approximately 65 years. 11,13,18,23,27,28,30,36,37,39,41,[43][44][45][83][84][85] Few patients have B symptoms or a performance status (PS) greater than 1, though these findings are rarely reported in published series. 11,18,28,30,42,84 Lacrimal gland and intraorbital sites, observed in approximately 50% of patients, are the most frequent ophthalmologic sites.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…29,87,88 In all published series except that by Cho et al, 42 the median age was approximately 65 years. 11,13,18,23,27,28,30,36,37,39,41,[43][44][45][83][84][85] Few patients have B symptoms or a performance status (PS) greater than 1, though these findings are rarely reported in published series. 11,18,28,30,42,84 Lacrimal gland and intraorbital sites, observed in approximately 50% of patients, are the most frequent ophthalmologic sites.…”
mentioning
confidence: 80%
“…11,13,18,22,23,27,28,[36][37][38][39][40][41][42][43][44][45][46][47] However, a large majority of reported OALs-between 95% and 100% of reported casescorrespond to the B-cell type, and 80% of B-cell lymphomas are low grade. A major characteristic of OAL is the high incidence of marginal zone B-cell lymphoma or mucosa-associated lymphoid tissue (MALT) lymphoma, reported in approximately 50% of patients.…”
Section: Histopathologic Characteristics Of Oalmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most common type is either follicular, 12% to 23%, or DLBCL, 7% to 21%, depending on the study. [4][5][6][7][8][9] The frequency of ocular adnexal lymphoma with localization to the orbit has been cited as 54%. 5 It has been suggested that it may be more appropriate to analyze ocular 10 found that for secondary ocular adnexal lymphoma, follicular type is most common (33%-66%) followed by (in approximate decreasing frequency) multiple myeloma/plasmacytoma, lymphoplasmocytic lymphoma/immunocytoma, mantle cell lymphoma, DLBCL, Burkitt lymphoma, MALT lymphoma and chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…The extranodal marginal zone B-cell lymphoma of mucosa-associated tissue (MALT lymphoma) represents the most common lymphoma subtype in the ocular adnexa (1,2). Ocular adnexal lymphomas, which arise in the conjunctiva, lacrimal gland, eyelid, and orbital connective tissue, account for 8-12% of all ocular adnexal tumors (3,4), and 8% of all extranodal non-Hodgkin lymphomas (NHL) (5).…”
Section: Introductionmentioning
confidence: 99%